New Hampshire - Thomas, William (Milwaukee, WI Gareth Stevens Publishing, 2007)
Someone traveling from north to south through New Hampshire will experience a wide variety of changing wildlife and scenery. Four distinct seasons offer vacationers a year-round choice of active pastimes.
5 - 9
Keywords: New Hampshire; Portraits of the States